SOFT COMPETENCY MAPPING TO IMPROVE ORGANIZATIONAL COMPETITIVENESS AND PERFORMANCE (CASE STUDY: STAFF LEVEL OF PT ABC) - Kartika, Luna
According to annual reports, PT ABC as a state-owned enterprise, experienced sequential decline in its KPI achievement as well as financial performance in 2019 and 2020. The decline is related to the difficulty they face in securing new projects, which was driven by the government APBN slowdown as well as growing competition from fellow state-owned company and private foreign companies. In order to tackle those challenges, company needs a strong support from its employees from all level, including staff, as the one delivering actions in the field. To support company in improving its performance, the staff should maximize the utilization of their skills and knowledge. To do so, employee should possess the necessary soft competencies which will drive and enable the staff to use their technical skills and knowledge to achieve goals. However, based on the preliminary survey, several complaints regarding employee soft competency were found in the company. On top of that, the employee soft competency management and development in PT ABC is still not optimal due to several factors including outdated soft competency model and lack of staff development programs that focus on soft competencies. Accordingly, author conducted soft competency mapping in PT ABC in order to help company in identifying the crucial soft competencies for staff and which competencies need to be improved.